Oszustwa księgowe w sprawozdaniach finansowych w opinii biegłych rewidentów - Prymon, Krzysztof (On some faults in financial measures in the light of opinions of chartered accountants, 2008)
The aim od the article is indication of some important faults in financial reporting. The article is based on the survey method. Questionnaires were run anong 48 haractered accountants. Research results show to what extent financial statements are reliable and what are basic weakness of accounting measures. Finally some recomendationd concering ways of improving the analysis of accounting measures are proposed.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 381-394